2010
DOI: 10.1007/s10157-009-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

A patient with Bartter syndrome accompanying severe growth hormone deficiency and focal segmental glomerulosclerosis

Abstract: Bartter syndrome is a rare autosomal recessive, salt-losing disorder characterized by hypokalemic hypochloremic metabolic alkalosis. A 10-year-old boy had severe growth retardation (height standard deviation score -8.15). He had a thin, triangular face, prominent ears and forehead, and big eyes. Megacystis, bilateral hydroureteronephrosis, and residual urine were detected in ultrasonography, but there was no vesicoureteral reflux. Lumbosacral magnetic resonance (MR) showed posterior disc bulging at L4-5. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Another factor may have been long-term treatment with non-steroidal antiinflammatory drugs [9]. In addition, Dent disease and Bartter syndrome themselves have been considered as possible causes of FGS [1,6,8,11]. Hypokalemic nephropathy might contribute to the development of end-stage renal failure in these patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another factor may have been long-term treatment with non-steroidal antiinflammatory drugs [9]. In addition, Dent disease and Bartter syndrome themselves have been considered as possible causes of FGS [1,6,8,11]. Hypokalemic nephropathy might contribute to the development of end-stage renal failure in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…Among them, the patient reported by Bogdanovic et al [3] also showed features of Bartter syndrome similar to our patient. Although the exact mechanism of the development of GHD is unknown, hypokalemia induces growth retardation through reduced circulating levels of GH and IGF-1 [1]. In addition, Bartter syndrome has been independently associated with GHD [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteinuria, a low glomerular filtration rate and 10 FSGS have been reported in BS and GS patients 22,37-39 . It has been suggested that FSGS is a 11 secondary lesion due to adaptation to salt loss, resulting in chronic stimulation of the renin-12 angiotensin system 37,39,40 . In the present study FSGS occurred in late stage of CKD suggesting 13 a large contribution of nephron reduction.…”
mentioning
confidence: 99%
“…Although BS is a typical tubular disorder, there have been several case reports of patients who developed focal segmental glomerulosclerosis (FSGS), a glomerular lesion, during the course of BS3-7). Such cases support a possible link between the two diseases, and indicate that stimulation of the renin-angiotensin system (RAS) and increased angiotensin II in response to chronic glomerular hyperfiltration due to salt-losing tubulopathy may lead to secondary FSGS3, 4, 8).…”
Section: Introductionmentioning
confidence: 99%